2020
DOI: 10.1101/2020.11.27.20239970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Willingness to vaccinate against COVID-19 in the US: Longitudinal evidence from a nationally representative sample of adults from April–October 2020

Abstract: IntroductionVaccines against COVID-19 have been developed in unprecedented time. However, the effectiveness of any vaccine is dictated by the proportion of the population willing to be vaccinated. In this observational population-based study we examined intentions to be vaccinated against COVID-19 over the course of the pandemic.MethodsWe analyzed longitudinal data from a nationally representative sample of 7,547 US adults enrolled in the Understanding America Study (UAS). Participants reporting being willing,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
78
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 27 publications
(55 reference statements)
18
78
2
3
Order By: Relevance
“…Consistent with other previous findings from the United States of America (USA) (27), Australia (28), and Turkey (29) concerning the acceptance of the COVID-19 and influenza vaccinations, this study found that concerns regarding the vaccine's safety and efficacy and fear of adverse reactions were the most important predictors of vaccine refusal. Healthcare workers have also identified the expedited vaccine trials as a reason for lack of intent to vaccinate.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with other previous findings from the United States of America (USA) (27), Australia (28), and Turkey (29) concerning the acceptance of the COVID-19 and influenza vaccinations, this study found that concerns regarding the vaccine's safety and efficacy and fear of adverse reactions were the most important predictors of vaccine refusal. Healthcare workers have also identified the expedited vaccine trials as a reason for lack of intent to vaccinate.…”
Section: Discussionsupporting
confidence: 90%
“…A survey in Ecuador showed that a very large proportion of individuals (at least 97%) were willing to accept a COVID-19 vaccine [ 18 ]. However, a study in the United States in October showed that the willingness to vaccinate was only 53.6% [ 19 ]. Our study found that 51.7% of the respondents who had children were willing to vaccinate their children.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of COVID-19 vaccination has thus been widely discussed in the current literature in different countries and regions [ 24 , 25 , 26 , 27 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. From a literature review, we found that most published studies focused on the COVID-19 vaccination willingness in general populations.…”
Section: Introductionmentioning
confidence: 99%
“…From a literature review, we found that most published studies focused on the COVID-19 vaccination willingness in general populations. More specifically, a relatively high rate of COVID-19 vaccination uptake willingness (49.7% to 91.3%) has been observed in the general populations in some Asian countries, including mainland China [ 35 ], Malaysia [ 37 ], and Indonesia [ 32 ]; some Europe countries, including Turkey, France, Italy, the UK, Ireland, Denmark, Germany, Portugal, and the Netherlands [ 33 ]; and the U.S. [ 34 , 41 , 50 ]. Low levels of willingness toward COVID-19 vaccination (27.0% to 29.4%) have been documented in general populations in Nigeria [ 28 ] and Arab countries, including Jordan, Kuwait, and Saudi Arabia [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation